Prenatal diagnosis of arachnoid cyst - Korkut Daglar; Ayse Kirbas; Ebru Biberoglu; Nuri Danisman (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2016)
Arachnoid cysts are rare, usually benign, space-occupying central nervous system lesion. They are the results of an accumulation of cerebrospinal-like fluid between the cerebral meninges and diagnosed prenatally as a unilocular, simple, echolucent area within the fetal head. They may be primary (congenital) (maldevelopment of the meninges) or secondary (acquired) (result of infection trauma, or hemorrhage). The primary ones typically dont communicate with the subarachnoid space whereas acquired forms usually communicate. In recent years, with the development of radiological techniques, the clinical detectability of arachnoid cysts seems to have increased. We report a case of primary arachnoid cyst that were diagnosed prenatally by using ultrasonography and magnetic resonance imaging . [Cukurova Med J 2016; 41(4.000): 792-795]